The 2 + 2 anisotropic Wilson gluon action with applications - PEARDON, MICHAEL JAMES; RYAN, SINEAD MARIE (My University, 2004)
A generalization of anisotropic lattices to include a 2+2 discretization is discussed. As a part of this program, we determine the one-loop correction to the gluon self-energy and analyse the restoration of Lorentz invariance in on-shell states for both the 2+2 and 3+1 cases. A 2+2 Wilson-like fermion action is also considered.
PUBLISHED
Keywords: Pure & Applied Mathematics